Two new species of the spider genus Pholcus Walckenaer, 1805 (Araneae, Pholcidae) from Tajikistan, with the first description of female Pholcus sidorenkoi Dunin, 1994 - Dong, Tingting; Zheng, Guo; Davlatov, Abdulaziz; Yao, Zhiyuan; Li, Shuqiang (European Journal of Taxonomy, 2017)
Two new species of the genus Pholcus Walckenaer, 1805 are described from Tajikistan: Pholcus saidovi Yao & Li sp. nov. (♂♀) and P. shuguanensis Yao & Li sp. nov. (♂). The female of P. sidorenkoi Dunin, 1994 is reported for the first time. All belong to the P. nenjukovi species group.